Dampak kelahiran prematur dan berat badan lahir rendah Terhadap risiko early childhood caries (ECC) - Putri Maharan, Febby; Putriany Agustin, Tri; D. Sjahruddin, Loes (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Premature birth and low birth weight (LBW) are conditions that can affects the dental health of children. Understanding the relationship between premature birth LBW factors with the risk of Early Childhood Caries (ECC) needs to be understood to identify the risk factors that may worsen a child’s dental health in the early stages of development. Purpose: To determine the impact pf premature birth and low birth weight (LBW) on the risk of early Childhood Caries (ECC). Method: This study uses an observational study design with a Scoping Review method following PRISMA guidelines on PubMed and Google Scholar databases. Result: An initial search yielded a total of 2.142 journals, and after exclusions based on inclusion criteria, 6 journals were identified as meeting the eligibility criteria and included in this study. Conclusion: Premature birth and LBW have the potential to increase the risk of ECC. This understanding can serve as a basis for efforts to prevent dental caries in children with a history of premature birth or LBW through appropriate dental health interventions and care.